Perioperative Blood Glucose Levels as a Predictor of Hospital Length of Stay in Complicated Appendicitis: A Prospective Cohort Study - Trengginas, Satrio Sarwo; Ida Bagus Budhi Surya Adnyana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Complicated appendicitis presents significant management challenges. Perioperative blood glucose levels are emerging as potential prognostic indicators in surgery. This study aimed to evaluate the correlation between perioperative blood glucose levels and hospital length of stay in patients with complicated appendicitis. Methods: This prospective cohort study was conducted at Dr. Moewardi General Hospital, Indonesia, from October 2020 to October 2021. We enrolled 49 adult patients with complicated appendicitis. Preoperative and postoperative blood glucose levels were measured. The primary outcome was hospital length of stay. Spearman’s correlation and ROC curve analyses were performed. Results: Significant positive correlations were found between hospital length of stay and preoperative blood glucose (r=0.324, p=0.023), postoperative blood glucose (r=0.484, p=0.000), age (r=0.324, p=0.023), and surgical site infection (r=0.360, p=0.011). Postoperative blood glucose showed the strongest correlation. ROC analysis identified a postoperative blood glucose level >123 mg/dL as a cut-off for prolonged hospitalization (>3 days), with 65.2% sensitivity and 65.4% specificity (AUC=0.71). Conclusion: Perioperative blood glucose levels significantly correlate with hospital length of stay in complicated appendicitis, with postoperative levels showing the strongest association. Monitoring postoperative blood glucose may help predict and potentially reduce the duration of hospitalization.